Growth Assessment and Nutritional Profiling of School-Aged Children: A Cross-Sectional Study - Muhammad Naveed Mazhar; Syed Hasan Danish; Muhammad Zaeem Khalid; Muhammad Karina Naveed; Farah Ahmad; Asghar Latif Shamsi (Medical Journal of South Punjab, 2024)
Introduction: Childhood malnutrition, encompassing both undernutrition and overnutrition, is a major public health issue. Regular growth monitoring using anthropometric indices is vital to evaluate the nutritional status of school-aged children and to guide intervention strategies. Material & Methods: A cross-sectional study was carried out on a sample of 1300 school children. Data collected included age, height, weight, and BMI. Nutritional status was assessed using WHO growth standards for Weight-for-Height (WFH) and Height-for-Age (HFA). Children were categorized into Severe, Moderate, and Mild Malnutrition, Normal, Overweight, Obese+, and Obese++. Results: Of the 1300 children examined, 14.3% were identified with severe wasting, 25.1% with moderate wasting, and 30.5% with mild malnutrition. Only 20.2% of children fell within the normal range. Overweight and obesity were found in 7.0%, 2.5%, and 0.4% of the children respectively. Conclusion: A significant proportion of the study population exhibited malnutrition, with a majority falling into various categories of undernutrition and a considerable portion affected by overnutrition. These findings underscore the need for regular nutritional surveillance and targeted health programs to address the dual burden of malnutrition in school-aged children.